F18-fluorodeoxyglucose-positron emission tomography and computed tomography is not accurate in preoperative staging of gastric cancer - Ha, Tae Kyung (The Korean Surgical Society, 2011)
PURPOSE: To investigate the clinical benefits of F18-fluorodeoxyglucose-positron emission tomography and computed tomography ((18)F-FDG-PET/CT) over multi-detector row CT (MDCT) in preoperative staging of gastric cancer. METHODS: FDG-PET/CT and MDCT were performed on 78 patients with gastric cancer pathologically diagnosed by endoscopy. The accuracy of radiologic staging retrospectively was compared to pathologic result after curative resection. RESULTS: Primary tumors were detected in 51 (65.4%) patients with (18)F-FDG-PET/CT, and 47 (60.3%) patients with MDCT. Regarding detection of lymph node metastasis, the sensitivity of FDG-PET/CT was 51.5% with an accuracy of 71.8%, whereas those of MDCT were 69.7% and 69.2%, respectively. The sensitivity of (18)F-FDG-PET/CT for a primary tumor with signet ring cell carcinoma was lower than that of (18)F-FDG-PET/CT for a primary tumor with non-signet ring cell carcinoma (35.3% vs. 73.8%, P < 0.01). CONCLUSION: Due to its low sensitivity, (18)F-FDG-PET/CT alone shows no definite clinical benefit for prediction of lymph node metastasis in preoperative staging of gastric cancer.